2021
DOI: 10.3390/atmos12091225
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric Delay in the Neapolitan and Vesuvius Areas (Italy) by Means of a Dense GPS Array: A Contribution for Weather Forecasting and Climate Monitoring

Abstract: Studying the spatiotemporal distribution and motion of water vapour (WV), the most variable greenhouse gas in the troposphere, is pivotal, not only for meteorology and climatology, but for geodesy, too. In fact, WV variability degrades, in an unpredictable way, almost all geodetic observation based on the propagation of electromagnetic signal through the atmosphere. We use data collected on a dense GPS network, designed for the purposes of monitoring the active Neapolitan (Italy) volcanoes, to retrieve the tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The distributions of weights of the cloud and/or precipitation profiles are displayed using violin plot diagrams (Barton et al, 2021; Riccardi et al, 2021; Thrun et al, 2020) as shown in Figure 4. Thanks to their representation of the probability density for each value of the distribution, these diagrams have the advantage of being able to represent multimodal distributions, unlike box plot diagrams.…”
Section: Methodsmentioning
confidence: 99%
“…The distributions of weights of the cloud and/or precipitation profiles are displayed using violin plot diagrams (Barton et al, 2021; Riccardi et al, 2021; Thrun et al, 2020) as shown in Figure 4. Thanks to their representation of the probability density for each value of the distribution, these diagrams have the advantage of being able to represent multimodal distributions, unlike box plot diagrams.…”
Section: Methodsmentioning
confidence: 99%
“…Extreme weather phenomena, such as heavy precipitation, typhoons, or storms [11], have been thoroughly assessed before using the horizontal tropospheric gradients, and it was generally found that the tropospheric parameters can represent the patterns followed by extreme weather phenomena. The effect of topography on water vapor distribution has been recently studied [12]. Water vapor variation was found to be associated with convective rainfall through an index derived from the tropospheric gradients [13], suggesting that the GPS-derived indices of water vapor inhomogeneity reflect local variation in water vapor associated with atmospheric convection.…”
Section: Introductionmentioning
confidence: 99%